Stabilization of the Distal Radioulnar Joint Using the TightRope Implant: A Distal Oblique Bundle Augmentation - Jawahier, Priscilla Alysha; Rahimtoola, Zulfi O.; Schep, N. W. L. (Journal of Wrist Surgery, 2023)
Background Triangular fibrocartilage complex (TFCC) injury often results in distal radioulnar joint (DRUJ) instability. However, not all patients with a ruptured TFCC have an unstable DRUJ as in these patients a distal oblique bundle (DOB) may be present. We assumed that augmentation of the DOB leads to a more stable situation following reinsertion of the TFCC. We present the clinical results of a new surgical technique using the TightRope system as a DOB augmentation.Description of Technique All cases were treated under regional anesthesia with the TightRope implant for which a tunnel was drilled from the distal ulna through the radius along the path of the DOB. The TightRope was passed through the tunnel and secured with buttons on either side. X-rays were made during surgery to confirm correct positioning.Methods A retrospective study was performed analyzing 21 cases treated with a TightRope augmentation of the DOB. The primary outcome was measured using the patient-rated wrist evaluation (PRWE) score at least 12 months after surgery.Results Postoperatively, the DRUJ was stable in all patients. The median PRWE score was 16 for the injured side compared to zero for the uninjured side (p-value: < 0.001). The median pronation and supination were not statistically significant when we compared the injured side to the uninjured side. The median grip strength was 31 kg for the injured side compared to 38 kg for the uninjured side (p-value: 0.015). There were two minor postoperative complications (10%).Conclusion This technique is capable of restoring DRUJ stability with a short immobilization period resulting in good patient-related outcomes and a low complication rate.
Keywords: distal radioulnar joint; triangular fibrocartilage complex; wrist stabilization; TightRope